Optimization model for sustainable food supply based on consumer behaviour typology. The case of the Chisinau urban area - Cosmulese, Cristina Gabriela; Socoliuc, Marian; Ciubotariu, Marius; Kicsi, Rozalia; Grosu, Veronica (Publishing House of Wroclaw University of Economics and Business, 2021)
The feature of a particular type of consumption that has developed over time at regional level has led to the development of certain characteristics of consumer behaviour that originate from structurally non-congruent regions. In this context, this study aims to develop a consumer behaviour optimization model, in order to design a sustainable supply as a stability factor for quality-focused food policies. The main objectives of the study focus on: an interpretative analysis of the specialist studies and of the present legislation both in Moldova and in the European Union in terms of food quality policies; an elaboration and application (between November 2018 and January 2019) of a questionnaire on a representative sample from among the population of the capital of Moldova – Chisinau; outlining the typological profile of the consumer; an optimisation of the typological profile of consumption by the reducing food risk factors. The findings refer to the elaboration of an optimisation model that can be used by producers for developing and ensuring the sustainable product offer on the food market
Argumenta Oeconomica, 2021, Nr 1 (46), s. 239-280